Photoshop for Video, 3rd Edition - Harrington, Richard (Routledge, 2012)
Master the graphic design and production skills required of today's video editors and motion graphic professionals with this comprehensive guide to the video tools in Adobe Photoshop CS3. Every page is filled with techniques to help the video professional make graphics for use in television, video, the Internet, and DVD. Lively discourse, full-color presentations, and hands-on tutorials demonstrate everything you need to know about how to combine still and moving images. Fundamental concepts such as transparency, pixel aspect ratio, and alpha channels are made precisely clear, and advanced techniques show how to use Photoshop as a character generator, color corrector, and animation tool. This edition features expanded coverage of DVD and motion graphics design, as well as addressing recent developments in High Definition video and 32-bit imaging. This indispensable reference includes: * real-world solutions for making graphics for video * introduction to third party plug-ins * automation and shortcut methods that cut production time * profiles of notable editors and motion graphic artists that include their favorite tips and tricks The DVD offers a hands-on multimedia experience with hundreds of images to work on, tutorials to complete and 2 ½ hours of video training to watch.